US-EU Trade War, Indonesian Exports Threatened to Be Dragged - A. Junaedi Karso (International Journal of Law and Society, 2025)
The reciprocal tariff policy has a significant impact on a number of countries, including Indonesia. In this scheme, Indonesian non-oil and gas products are subject to a tariff of 32% when entering the US market. Such a high tariff places Indonesian exporters in a less competitive position compared to other countries that have more favorable trade arrangements with the United States. This condition becomes more complex when viewed in the broader context of the US-EU trade war, which creates uncertainty and turbulence in the global economy. Indonesian exports are affected both directly and indirectly. Indirect impacts can be seen from disruptions to the global supply chain, the slowdown in the world economy, and decreased global demand. As global production networks become increasingly interconnected, any disruption in major economies will ultimately suppress demand for Indonesian export commodities. This means that even if Indonesian products are not directly targeted, the ripple effects of global trade tensions will still hinder Indonesia’s export performance. For instance, reduced consumption in Europe and the US due to rising product prices and inflation will diminish market opportunities for Indonesian goods.On the other hand, direct impacts arise because several Indonesian products have been explicitly subjected to tariffs by the US government. These include textiles and textile products (TPT), electronics and their components, footwear, furniture, and palm oil (crude palm oil/CPO). Such tariffs significantly reduce Indonesia’s competitiveness in the US market, potentially leading to decreased export volumes, lower revenues for domestic industries, and job losses in export-oriented sectors. Furthermore, the policy also makes European products much more expensive in the US market, which worsens the global supply chain, increases logistics costs, triggers inflation, and escalates uncertainty in international trade.